Characterization of visual symptoms of nutritional deficiencies in oak seedlings - Sepúlveda, Yira Lucia (2014)
The identification of visual symptoms of deficien- cies is a widely used method in the diagnosis of nutritional problems in agricultural and forestry production. The aim of this study was to charac- terize visual symptoms of deficiencies of N, P, K, Ca, Mg, S and B, in seedlings of the andean oak, Quercus humboldtii Bonpl., under nursery conditions. Seedlings were planted in polythene bags, where fertility treatments were applied according to the method of Jenny. After 4 months of development, we photographed seedlings and leaves with symptoms of nutritional deficiencies and determined leaf nutrient content. Deficiency symptoms were detected for all nutrients studied, except B. Seedlings deficient in each nutrient had lower concentration of this element in leaf tissues. The applied dose of P was apparently not enough to have an adequate availability of this nutrient and to generate an optimal development of seed- lings of Q. humboldtii under full fertilization.